FEATURES OF THE GAUSSIAN BEAM INTENSITY PROFILE WITHIN THE PARAXIAL APPROXIMATION - Урозов Абдухолик Нурмаматович; Абдувасиев Сардор Бахромович (Journals Park Publishing, 2024)
The intensity of the Gaussian ray corresponds to the curve of the normal distribution in free space. As it spreads, divergence and width increase with distance. Using the paraxial approximation, the effect of distance on intensity, width, radius of curvature and divergence was investigated. The Matlab program was used to calculate the parameters of the characteristics. The result obtained in this work indicates smaller angles of divergence, which can provide better beam quality and intensity. Finally, it will be of great importance for applications such as pointing, optical communication in free space, etc.
Keywords: Gaussian beam, paraxial approximation, ray divergence, normal distribution curve